Clinical profile, dietary zinc content, and lifestyle habits of adult male and female hbss and hbsc patients (Bangladesh Journal of Medical Science, 2024)
Objective: Males and females have been reported to show significant variation with respect to clinical profile of sickle cell disease (SCD) (e.g. cardiovascular, musculoskeletal and chronic end-organ complications). Clinical features of SCD are also influenced by lifestyle and dietary habits. Thus, the study was conducted to examine whether the distributions of other manifestations (e.g. priapism, pain frequency, leg ulcers rates) and habits (lifestyle, dietary) of SCD patients in Osun state, Nigeria are influenced by gender or genotype.Material and methods: Questionnaires were administered to obtain information on age, gender, concoction/herbal preparations, and fruit/vegetable consumption, as well as zinc contents of 24-hour meal recall, physical exercise, lifestyle parameters and clinical profile of SCD. Descriptive (relative frequency) and inferential (Chi-square (χ2) test of independence) statistics were employed. Statistical significant was set at p